2020
DOI: 10.3389/fvets.2020.00104
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of miRNAs in Hypoxia (“HypoxamiRs”) in Three Canine High-Grade Glioma Cell Lines

Abstract: Dogs with spontaneous high-grade gliomas increasingly are being proposed as useful large animal pre-clinical models for the human disease. Hypoxia is a critical microenvironmental condition that is common in both canine and human high-grade gliomas and drives increased angiogenesis, chemo-and radioresistance, and acquisition of a stem-like phenotype. Some of this effect is mediated by the hypoxia-induced expression of microRNAs, small (∼22 nucleotides long), non-coding RNAs that can modulate gene expression th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 102 publications
(111 reference statements)
0
7
0
Order By: Relevance
“…In order to assess the growth of our newly established patient derived lines, we sought to compare them to the canine SDT‐3G, G06‐A, (both high‐grade astrocytoma) and J3T‐Bg (anaplastic astrocytoma) cell lines which are commonly used by the veterinary community 16,19,20 . We assessed in vitro cell growth using the IncuCyte live cell imaging system to capture images of cells over time and calculate growth as a measure of confluence, normalized to the first time point (Figures 4A and S1c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to assess the growth of our newly established patient derived lines, we sought to compare them to the canine SDT‐3G, G06‐A, (both high‐grade astrocytoma) and J3T‐Bg (anaplastic astrocytoma) cell lines which are commonly used by the veterinary community 16,19,20 . We assessed in vitro cell growth using the IncuCyte live cell imaging system to capture images of cells over time and calculate growth as a measure of confluence, normalized to the first time point (Figures 4A and S1c).…”
Section: Resultsmentioning
confidence: 99%
“…In order to assess the growth of our newly established patient derived lines, we sought to compare them to the canine SDT-3G, G06-A, (both high-grade astrocytoma) and J3T-Bg (anaplastic astrocytoma) cell lines which are commonly used by the veterinary community. 16,19,20 We assessed in vitro cell growth using the IncuCyte live cell imaging system to capture images of cells over time and calculate growth as a measure of confluence, normalized to the first time point (Figures 4A and S1c). The novel patient-derived lines Mo-HO and Boo-HA exhibit the slowest growth, with doubling times of 128 and 42 h respectively, whereas SDT-3G, J3T-Bg and G06-A are faster growing with doubling times of 36, 22, and 18 h, respectively.…”
Section: Growth Of Mo-ho and Boo-ha Patientderived Lines In Vitromentioning
confidence: 99%
“…An earlier study reported that NCL transcripts were regulated by microRNA-494 (miR-494) 45 . Notably, miR-494 has a HRE in its promoter ( Supplementary Fig.9 ) and was previously reported to be induced under hypoxic conditions 46,47 . To examine this hypothesis, we measured miR-494 levels in Calu-3 cells cultured at 1% oxygen or treated with Daprodustat and found a robust induction ( Fig.4e ).…”
Section: Resultsmentioning
confidence: 92%
“…Overexpression of miR-210 was documented in pancreatic, head and neck, breast and lung cancers [ 266 ]. Similar to miR-210, miR-323 is upregulated in hypoxia, and its low levels are connected to longer survival in human glioblastoma patients [ 267 ]. Although miR-137 functions as a tumour suppressor [ 268 ], it also plays a role in hypoxia and inhibition of ROS accumulation; miR-137 directly downregulates the expression of the hypoxia-mediated mitophagy receptors FUNDC1 and NIX, leading to suppression of apoptosis and mitophagy [ 253 ].…”
Section: Mirna Regulation Of Mitochondrial Genesmentioning
confidence: 99%
“…MiR-216b inhibits proliferation and cell invasion in several types of cancer and is downregulated in hypoxia. Low levels of this miRNA were associated with poor prognosis [ 267 ].…”
Section: Mirna Regulation Of Mitochondrial Genesmentioning
confidence: 99%